STUDENTS’ PRAGMATIC AWARENESS IN COMPREHENDING WRITTEN DISCOURSE OF ENGLISH DEPARTMENT OF IAIN BUKITTINGGI - Nofa Minanda; Eliza Eliza; Merry Prima Dewi (ELP (Journal of English Language Pedagogy), 2020)
Knowledge of pragmatic has been crucial element to the students English Department. The main focus of the research to find out the level of students pragmatic awareness by using percentage, the research was due to the problem found some students still used inappropriate respond to the pragmatic situation. The design of this research was a descriptive quantitative research in which the sample was taking by using random sampling technique with 25 samples at IAIN Bukittinggi of English Department. Additionally, the analyzing of the data was done by Written Discourse Completion Test (WDCT) test which is consist of 17 situation, made the description about the students pragmatic awareness in comprehending written discourse, analyzing the data using percentage, describe the data, found the level and making conclusion. The result showed that students pragmatic awareness in comprehending term in deixis is 61% it means the level is good. In performing term of speech act is 79% it means the level is good. Moreover, in understanding maxim is 62% it means the level is good. All of the students pragmatic awareness in comprehending written discourse is 67% it means the pragmatic awareness in comprehending written discourse of English Department of IAIN Bukittinggi is good. The implication of this study to know the level of pragmatic awareness in written discourse of English Department of IAIN Bukittinggi.